On linguistic properties of verbal number systems: A cross-linguistic study of number transcoding errors observed in a Basque–French bilingual patient with aphasia. - Pourquié, Marie; Nespoulous, Jean-Luc (Lingua, 2018)
The present study aims to assess the assumption that number transcoding processing is driven by the linguistic properties of verbal number systems, through the analysis of errors produced by a Basque–French bilingual adult with aphasia, in a number dictation task. In particular, it was predicted that errors would not be the same in Basque and French given their respective differences in the formation of numbers (Basque has a vigecimal regular system whereas French has a decimal irregular system). A 44-year-old Basque–French bilingual patient with aphasia, and a control subject, were assessed on a dictation task. The task consisted in hearing Basque or French numbers, and writing them in Arabic numerals. Results show that the patient produced different errors in each language. The errors can be explained in terms of the different linguistic properties of the Basque and French numeral systems. That this could be observed in one and the same bilingual individual, whose two languages use different numeral systems, suggests the involvement of distinct transcoding processes respective to the particular language in which numbers are being processed. This highlights an interaction between language and number representation and processing, a new and active field of inquiry in contemporary cognition research.